Decreased hepatocellular carcinoma tumor burden with the achievement of hepatitis C virus sustained virologic response: unlocking the potential of T-cell-mediated immunosurveillance - Griffith, Anna S (J Hepatocell Carcinoma, 2018)
We describe two cases of patients with hepatitis C virus (HCV) treated with direct-acting antiviral (DAA) therapy who had dramatic improvement in hepatocellular carcinoma (HCC) tumor burden with DAA therapy alone. Both patients were diagnosed with HCC on screening magnetic resonance imaging shortly after beginning DAA therapy. Both patients achieved sustained virologic response (SVR) with dramatic improvement in HCC tumor burden on follow-up imaging without HCC treatment. Patients with multifocal or advanced HCC are infrequently treated with antiviral therapy for HCV. As a result, these cases provide unique insight into the ongoing debate regarding the impact of SVR on existing and recurrent HCC. We review the current literature regarding this debate, as well as the theory of immunosurveillance. We postulate that DAA therapy activates CD8(+) T cells to induce a T-cell-mediated response and increased immunosurveillance to virus-induced liver cancer.